Effect of sorghum bran incorporation on the physicochemical and microbial properties of beef sausage during cold storage. (February 2022) - Xiong, Yun; Zhang, Pangzhen; Warner, Robyn Dorothy; Hossain, Md Nur; Leonard, William; Fang, Zhongxiang
Abstract: Sorghum bran is a rich source of phenolic compounds with potent antioxidant and antimicrobial properties. This study investigated the effect of brown and black sorghum bran incorporation on the physicochemical and microbiological properties of beef sausages during cold storage at 4 °C. Results showed that the incorporation of sorghum bran in sausages, unexpectedly, promoted sausage discolouration, oxidation and pH fluctuation. The addition of sorghum bran in sausages significantly increased the texture values, including hardness, cohesiveness, resilience, gumminess and chewiness. In sorghum-added sausages, the total plate count, yeast & moulds count, and total Coliforms were inhibited only for the first 5–10 days, followed by a rapid increase, whilst the pathogenic Escherichia coli and Listeria spp. were inhibited throughout storage. Brown and black sorghum bran treatments had similar effects on sausages, and the effects were dependent on the amount of bran added. Although this study did not confirm the antioxidant effect of sorghum bran in meat application, it did demonstrate that sorghum bran has some antimicrobial activity, both of which require further evidence for verification. Highlights: Sorghum bran addition promoted sausage discolouration, oxidation and pH fluctuation. Sorghum bran addition enhanced the sausage texture. Sorghum bran addition showed some antimicrobial activity. Brown and black sorghum bran showed similar effects on sausage quality.